Thinning strategies for maritime pine (Pinus pinaster Ait.) in Portugal - Oliveira, Ângelo Carvalho (2019)
To establish a thinning strategy for maritime pine stands (Pinus pinaster Ait) basal area, Wilson relative spacing index (WILSON, 1946), Reineke spacing density index (REINEKE, 1933) and Curtis relative density (CURTIS, 1982) are compared. Reineke’s index was chosen to elaborate a field guide for thinnings in maritime pine stands